Empowering youth and ensuring health: utilization of youth friendly service among preparatory school students in Gambella, Southwest Ethiopia - Hailu, Nardos; Negero, Benti; Melkamu, Keno; Tsega, Yawkal (Frontiers in Reproductive Health, 2024)
BackgroundYouth is a period with exposure to high risk of reproductive health (RH) problems. Despite, several strategies designed to solve these problems, youths are experiencing unsafe abortion, unintended pregnancy, and sexually transmitted infections (STIs) so far. The utilization of Youth Friendly Services (YFS) and its determinants has not been well studied in Gambella so far. This study aimed to assess YFS utilization and associated factors among preparatory school students in Gambella town, Southwest Ethiopia.MethodsInstitution based cross-sectional study was conducted on 394 randomly selected preparatory school students in Gambella town from June 1-30/2023. Data were collected through self-administered questionnaire, entered to EpiData version 4.6, and exported to Stata version 17.0 statistical software for analysis. Bivariable and multivariable logistic regression analyses were employed. The p-value of <0.05 with 95% CI was used to declare statistical significance of association between YFS utilization and explanatory variables.ResultLess than one third (31.2%) of preparatory school students utilized YFS in Gambella town. Being married (AOR: 4.94, CI: 2.14, 11.38), having pocket money (AOR: 2.02, CI: 1.15, 3.56), no payment for YFS (AOR: 2.13, CI: 1.01, 4.50), having knowledge about YFS (AOR: 2.27, CI: 1.29, 4.00), convenient working time (AOR: 2.50, CI: 1.08, 5.83), and sexual experience (AOR: 3.38, CI: 1.90, 6.01) were the factors significantly associated with utilization of YFS in Gambella town.ConclusionThe study found that utilization of YFS in Gambella town was low. Being married, having pocket money, not asked payment for YFS, knowledge about YFS, convenient working time, and sexual experience were the factors positively affecting utilization of YFS in Gambella town. Therefore, the health decision makers better to design policies aimed to increase youths knowledge about YFS.